(untitled) - Hamel, Gary (Boston, 1994)
Contents: Getting off the treadmill; Learning to forget; strategy as stretch; strategy as leverage; Securing the future.
Keywords: Competition,Competition international,Sự cạnh tranh,Cạnh tranh quốc tế